2018
DOI: 10.3389/fimmu.2018.01383
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelial Progenitors in the Repair of Vascular Damage in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a connective tissue disease characterized by a complex pathological process where the main scenario is represented by progressive loss of microvascular bed, with the consequent progressive fibrotic changes in involved organ and tissues. Although most aspects of vascular injury in scleroderma are poorly understood, recent data suggest that the scleroderma impairment of neovascularization could be related to both angiogenesis and vasculogenesis failure. Particularly, compensatory angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 107 publications
1
36
0
Order By: Relevance
“…Consistent with our findings, endothelial progenitor cells (EPC) with impaired angiogenic function have been detected in peripheral blood of SSc subjects [68], and the regression of capillaries and small vessels during SSc strongly suggests an impairment in the angiogenetic abilities of endothelial cells, although the specific mechanisms have not yet been elucidated.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our findings, endothelial progenitor cells (EPC) with impaired angiogenic function have been detected in peripheral blood of SSc subjects [68], and the regression of capillaries and small vessels during SSc strongly suggests an impairment in the angiogenetic abilities of endothelial cells, although the specific mechanisms have not yet been elucidated.…”
Section: Discussionsupporting
confidence: 88%
“…In systemic sclerosis (SSc), the main pathogenic scenario is represented by early endothelial cell injury and microvascular desertification culminating into skin and internal organ fibrosis 1. Growing evidence suggests that impaired vascular repair and neovascularisation could be related to failure of both angiogenesis and endothelial progenitor cell (EPC)-driven vasculogenesis 2…”
mentioning
confidence: 99%
“…In SSc, the majority of studies are focused on the role of blood vessel dysfunction,1 2 while the involvement of the lymphatic microcirculation has attracted much less attention. Nevertheless, clinical and histological findings have shown that lesional SSc skin displays lymphatic circulatory abnormalities 3–5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In SSc, great emphasis has traditionally been placed on blood vessel dysfunction and defective angiogenesis and vascular repair, while the involvement of the lymphatic vascular counterpart has been mostly overlooked [5][6][7][8]. Nonetheless, a few clinical and histopathologic studies have demonstrated that clinically-affected SSc skin displays lymphatic microvascular abnormalities, including a severe reduction in both superficial and deep dermal microlymphatic networks that has been correlated with the presence of fingertip ulcers and linked to cutaneous disease progression from an early edematous stage toward overt fibrotic remodeling [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%